A PROSPECTIVE STUDY OF IMPLICATIONS OF STRUCTURED REPORTING ON OESOPHAGEAL CANCER, ANDHRA PRADESH, INDIA. - Surya, Duddu Gowtham; Reddy, Chintakunta Gurivi; Sheethal, Gonapati; Tadicherla, Rani (Student’s Journal of Health Research Africa, 2023)
Background To enhance clinical results, oesophageal carcinoma, a major cause of death that affects millions of people globally, needs a personalised treatment plan based on the disease’s particular stage. The study aimed to evaluate the influence of incorporating a structured report template on the excellence of computed tomography reports pertaining to cases of oesophageal carcinoma. Methods This prospective study, conducted at Siddhartha Medical College, involved 60 confirmed cases of oesophageal carcinoma from January to November 2023. Two radiologist’s utilized distinct reporting methods, with one employing a structured format, adhering to the seventh edition of ‘TNM Staging System for Oesophageal Cancer,’ while ethical considerations and potential biases were addressed in data collection and analysis. Results In this study involving 60 patients, adenocarcinoma (AC) was diagnosed in 40 individuals, and squamous cell carcinoma (SCC) in 20, with a median age of 64 for both groups, predominantly affecting men. Treatment patterns revealed over 72.7 % utilization of radiation therapy for SCC, while surgery was frequently recommended for AC. The structured reporting template significantly enhanced the overall understanding of oesophageal carcinoma cases, with surgeons expressing a clear preference for the structured format, particularly in cases where it proved more effective in providing necessary details for surgical planning. Conclusion This study underscores the efficacy of a structured reporting template in enhancing diagnostic clarity for oesophageal carcinoma. Surgeons exhibited a preference for this format, emphasizing its potential for improved comprehension and surgical planning. Recommendation The study recommends the widespread adoption of structured reporting templates for oesophageal carcinoma to optimize diagnostic understanding. Further integration and training on structured reporting are advised to enhance its effectiveness in clinical practice.